Impact of a 40‐Gene Targeted Panel Test on Physician Decision Making for Patients With Acute Myeloid Leukemia. (December 2021) - Barnell, Erica K.; Newcomer, Kenneth F.; Skidmore, Zachary L.; Krysiak, Kilannin; Anderson, Sydney R.; Wartman, Lukas D.; Oh, Stephen T.; Welch, John S.; Stockerl‐Goldstein, Keith E.; Vij, Ravi; Cashen, Amanda F.; Pusic, Iskra; et al.
Abstract : PURPOSE : Physicians treating hematologic malignancies increasingly order targeted sequencing panels to interrogate recurrently mutated genes. The precise impact of these panels on clinical decision making is not well understood. METHODS : Here, we report our institutional experience with a targeted 40‐gene panel (MyeloSeq) that is used to generate a report for both genetic variants and variant allele frequencies for the treating physician (the limit of mutation detection is approximately one AML cell in 50). RESULTS : In total, 346 sequencing reports were generated for 325 patients with suspected hematologic malignancies over an 8‐month period (August 2018 to April 2019). To determine the influence of genomic data on clinical care for patients with acute myeloid leukemia (AML), we analyzed 122 consecutive reports from 109 patients diagnosed with AML and surveyed the treating physicians with a standardized questionnaire. The panel was ordered most commonly at diagnosis (61.5%), but was also used to assess response to therapy (22.9%) and to detect suspected relapse (15.6%). The panel was ordered at multiple timepoints during the disease course for 11% of patients. Physicians self‐reported that 50 of 114 sequencing reports (44%) influenced clinical care decisions in 44 individual patients. Influences were often nuanced and extended beyond identifying actionable genetic variants with US Food and Drug Administration‐approved drugs. CONCLUSION : This study provides insights into how physicians are currently using multigene panels capable of detecting relatively rare AML cells. The most influential way to integrate these tools into clinical practice will be to perform prospective clinical trials that assess patient outcomes in response to genomically driven interventions.